2005
DOI: 10.1103/physrevb.72.214519
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in the vicinity of the surface ofκ(BEDTTTF)2Cu[N(CN

Abstract: Partial suppression of superconductivity by fast cooling has been observed in the organic superconductor κ-(BEDT-TTF)2Cu[N(CN)2]Br by two means: a marked sample size effect on the magnetic susceptibility and direct imaging of insulating regions by scanning microregion infrared reflectance spectroscopy. Macroscopic insulating regions are proposed in the vicinity of the crystalline surface after fast cooling, with diameters of 50-100 µm and depths of a few µm. The very large in-plane penetration depth reported t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…This is considered to be the reason why the present system at 4.3 kbar shows the coexistence. We note that, also in the quasi-twodimensional organic system -͑BEDT-TTF͒ 2 X, 16 the coexistence of bulk insulating and metallic phases is observed near the first-order Mott transition, 17,18 which is very likely due to the same reason.…”
Section: B Schematic Phase Diagrammentioning
confidence: 68%
“…This is considered to be the reason why the present system at 4.3 kbar shows the coexistence. We note that, also in the quasi-twodimensional organic system -͑BEDT-TTF͒ 2 X, 16 the coexistence of bulk insulating and metallic phases is observed near the first-order Mott transition, 17,18 which is very likely due to the same reason.…”
Section: B Schematic Phase Diagrammentioning
confidence: 68%
“…The samples were cooled down in a He-flow cryostat. The cooling rates were in the range from 0.2 K/min to 1 K/min so as to avoid a mixed state of metallic and insulating domains in κ-ET-Br 25,26 . The absence of luminescence at 3500 cm −1 proved that κ-ET-Br is in a homogeneous metallic state 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Further study is needed to clarify the effect of the cooling rate on the inhomogeneity of the sample and its distribution. This is important for resolving the controversy regarding superconducting parameters such as the penetration depth [14]. …”
Section: Phase Separation In the Vicinity Of The Surface By Rapid Coomentioning
confidence: 99%
“…In this article, we review the visualization of the spatial phase separation observed in the organic dimer Mott system κ-(BEDT-TTF) 2 X [12][13][14][15]. To achieve sufficient spatial resolution, a synchrotron is used as the infrared light source [16].…”
Section: Introductionmentioning
confidence: 99%